2016
DOI: 10.2500/ajra.2016.30.4393
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Innate Immune Response Gene Regulation in the Middle Ear of Children who are Otitis Prone and in those not Otitis Prone

Abstract: Innate-immune response genes are differentially regulated in children who were sOP compared with children with NOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Thus, it is tempting to speculate that the gender-based differences in inflammatory markers may relate to the chronicity of OME. It is also interesting to note that otitis-prone children have been shown to display significant downregulation of several factors involved in innate immune responses, further emphasizing the importance of well-regulated immune responses(22).Innate immune cells (such as neutrophils and monocytes-macrophages) are among the first leukocytes to be recruited to sites of infection, but were observed in this study to clearly predominate and associate with a higher degree of inflammation also in the chronic situationof OME. The innate immune cell predominance significantly correlated with a vast array of inflammatory mediators.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Thus, it is tempting to speculate that the gender-based differences in inflammatory markers may relate to the chronicity of OME. It is also interesting to note that otitis-prone children have been shown to display significant downregulation of several factors involved in innate immune responses, further emphasizing the importance of well-regulated immune responses(22).Innate immune cells (such as neutrophils and monocytes-macrophages) are among the first leukocytes to be recruited to sites of infection, but were observed in this study to clearly predominate and associate with a higher degree of inflammation also in the chronic situationof OME. The innate immune cell predominance significantly correlated with a vast array of inflammatory mediators.…”
mentioning
confidence: 53%
“…Thus, it is tempting to speculate that the gender-based differences in inflammatory markers may relate to the chronicity of OME. It is also interesting to note that otitis-prone children have been shown to display significant downregulation of several factors involved in innate immune responses, further emphasizing the importance of well-regulated immune responses ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their series of 121 patients, 42.5% (73) with a previous diagnosis of nonallergic rhinitis were ultimately found to have positive reactions to grass (Phleum partense), Artemisia, and birch pollen based on skin-prick testing and serum specific IgE measurements. Furthermore, in the study by Kaur et al, 14 innate immune genes analysis of middle ear fluid samples revealed differential expression in children who were otitis prone versus non otitis prone children.…”
mentioning
confidence: 99%
“…Using a CFX Real-Time touch PCR System thermo-cycler (Biorad, Melbourne Australia) and Qiagen prescribed cycle, the relative gene/mRNA expression of ST285-treated monocytes were analyzed in contrast to control untreated monocytes. The RT 2 qPCR innate and adaptive immune response arrays targeted a set of 84 innate and adaptive immune-related genes, five housekeeping genes, anRT control, a positive PCR control, and a human genomic DNA contamination control[29].…”
mentioning
confidence: 99%